Development and Definition of Prambanan Temple Deformation Monitoring Control Points - Rochmad Muryamto; Muhammad Iqbal Taftazani; Yulaikhah Yulaikhah; Bambang Kun Cahyono; Anindya Sricandra Prasidya (Universitas Gadjah Mada, 2019)
Since 1991, Prambanan Temple has been recognized by UNESCO as a cultural heritage of a historic building. In its construction, the Prambanan temple was established in a labile soil structure in the sandy soil and not far from the Opak River. In the geological map of Yogyakarta, there is a fault under the Opak River landscape. This fault under the Opak River has caused an earthquake in 2006. Because of its position in disaster-prone areas, regular monitoring of the geometric aspects of Prambanan Temple is very necessary.This research aims to build a deformation monitoring control point in Prambanan Temple. Eight control points, consist of three existing points and five new points are built around Prambanan Temple. These eight control points then were measured by observing GNSS for 1x24 hours in order to define their coordinates. GNSS data processing is done using GAMIT 10.70 software with two strategies, namely (1) processing with regional binding points, in this case using IGS BAKO and JOG2 stations, and (2) processing with global binding points using IGS COCO station reference points, DARW, KARR, POHN, PIMO, DGAR, and IISC. This research yields the establishment of Prambanan temple deformation control points and their coordinates and standard deviation in two processing strategies. The smallest standard deviation in the first strategy is 0.0787 m on the Z-axis for points of PRO1 and PR03. The biggest standard deviation is 0.1218 m on the Y-axis at point of PR02. In the second strategy the smallest standard deviation is 0.0036 m on the Z-axis for points of PR01 and PR03. The biggest standard is 0.0141 m on the Y-axis at point of PR02.